Liberty: Security dilemmas and party cohesion in the European Parliament*. (4th February 2019) - Chiru, Mihail; Stoian, Valentin
Abstract: The European Parliament is an increasingly central actor in attempts to regulate surveillance and find the balance between safeguarding personal freedoms and ensuring EU citizens' security. However, virtually nothing is known about what drives the positions of MEPs on this issue, or about how the cohesion of European parties is affected by these attempts. We explore this subject and propose a novel theoretical framework focusing on the interplay between the characteristics of the two principals of the MEPs – European party groups and national parties. We tested the model by analysing the votes held on the two most salient directives adopted in this field. The findings indicate that national parties' ideological positions, and the differences between them and the European parties in the salience assigned to human rights and law and order, predict to a great extent both MEP votes on the directives and dissent from the European party line.